The death of Slim Shady : (coup de grâce) [compact disc] - Eminem, 1972- (Shady Records ; Aftermath Records ; Interscope Records, 2024)
Eminem delves into unchartered territories, exploring the demise and rebirth of his iconic alter ego. With raw lyrical prowess and captivating storytelling, Eminem delivers an emotional rollercoaster that showcases his evolution.